Polarization phenomena initiated by electromagnetic interactions of particles with nuclei - V. K. Tartakovsky (Ядерна фізика та енергетика)
Polarization phenomena in the processes induced by electromagnetic interaction of photons, electrons, nucleons and certain composite particles with nuclei are studied. Calculations of the polarizations and related quantities have been performed and the obtained results have been discussed along with comparing existing experimental data to reveal possibilities for extracting new information on nuclei and the NN interaction. Presentation contains concise fragments from other works on the subject under consideration.